2022
DOI: 10.1002/2211-5463.13461
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin promotes macrophage efferocytosis and ameliorates lung inflammation via the ERK5/Mer signaling pathway

Abstract: Acute lung injury (ALI) is a pneumonic response characterized by neutrophil infiltration. Macrophage efferocytosis is the process whereby macrophages remove apoptotic cells, and is required for ALI inflammation to subside. The glycoprotein ulinastatin (UTI) has an anti-inflammatory effect during the acute stages of ALI, but its effect on efferocytosis and the subinflammatory stage of ALI is unclear. Extracellular signal-regulated kinase 5 (ERK5) is a key protein in efferocytosis, and we thus hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…33 Additionally, UTI can also influence the expression levels of ERK/MER, affecting macrophage apoptosis, thereby impacting immune-inflammatory responses. 42 It is worth noting that oxidative stress is closely associated with inflammatory responses. Studies have demonstrated that oxidative stress leads to an excessive generation of ROS and a decrease in the levels and activity of antioxidant enzymes, resulting in an imbalance between the oxidative and antioxidant systems.…”
Section: Discussionmentioning
confidence: 99%
“…33 Additionally, UTI can also influence the expression levels of ERK/MER, affecting macrophage apoptosis, thereby impacting immune-inflammatory responses. 42 It is worth noting that oxidative stress is closely associated with inflammatory responses. Studies have demonstrated that oxidative stress leads to an excessive generation of ROS and a decrease in the levels and activity of antioxidant enzymes, resulting in an imbalance between the oxidative and antioxidant systems.…”
Section: Discussionmentioning
confidence: 99%
“…ERK5 is a key protein in macrophage endocytosis. The glycoprotein ulinastatin (UTI) increases ERK5 levels, enhances endocytosis through the ERK5/Mer signaling pathway, and reduces lung inflammation and injury [47]. However, some studies present contrasting findings.…”
Section: Lungmentioning
confidence: 99%
“…Considering the transition from the early postlesional inflammatory stage to the subsiding phase leading to and remodeling of the lung structure, the role of ulinastatin was shown to promote the process of efferocytosis, namely the clearing process of apoptotic neutrophils operated by macrophages to favor repair [ 76 ].…”
Section: Conclusion and Summary Of Unknown Points To Be Addressed In ...mentioning
confidence: 99%